CULTURAL RELATIONS OF THE BUKHARA JEWISH CONGRESS OF THE USA AND CANADA WITH UZBEKISTAN - Botirov Sarvar Bahrom o‘g‘li; Botirov Sarvar Bahrom o‘g‘li (Western European Studies, 2024)
During the years of independence, many diasporas emerged, creating favorable conditions for Jewish emigration to Israel, the USA, and European countries. Bukhara Jews who moved from Uzbekistan to the USA 30, 20, 15, or 10 years ago have not only preserved their entire lifestyle and national-ethnic and religious heritage from Uzbekistan but have also created a completely different socio-economic and cultural environment. The Uzbekistan – USA Friendship Society, under the Committee for Interethnic Relations and Friendship Affairs of the Ministry of Foreign Affairs of the Republic of Uzbekistan, plays a key role in these processes.
Keywords: Foreign; lifestyle; Affairs; countries